Euroscepticism, Europhobia and Eurocriticism : The Radical Parties of the Right and Left vis-à-vis" the European Union" - Rodríguez-Aguilera de Prat, Cesáreo (2013)
This book analyses in detail the electoral manifestos and programmes presented by twenty-two parties during the European Parliamentary elections in 2009. The research indicates that radical right-wing parties usually have Europhobic impulses, however, radical left-wing parties are, in theory, favourable to European integration, but dispute the direction currently imposed by the EU authorities.